Hydrodynamics and loadings of tsunami waves with different fluid characteristics: Newtonian & non-Newtonian - Mohd Sahimy, Mohamad Razman (IRC, 2016)
Tsunamis are impulsively generated waves which may severely damage structures within the coastal zones. Damage may occur to protective structures, port and waterfront facilities, and commercial and residential structures. As a result, major damages occurs from the force of the tsunami, from flooding, or from impacts of waterborne debris. Tsunami waves that propagates shoreward frequently connected with sediment and debris, either the ones existing on the shorelines or carried away by the waves from afar.